Farmers' perceptions, preferences, and propositions for result-oriented measures in mountain farming. (January 2018) - Wezel, Alexander; Vincent, Audrey; Nitsch, Heike; Schmid, Otto; Dubbert, Monika; Tasser, Erich; Fleury, Philippe; Stöckli, Sybille; Stolze, Matthias; Bogner, Daniel
Highlights: We interviewed 79 farmers from 5 countries regarding result-oriented measures. A majority of farmers stated preference for result-oriented measures. It is seen as easier to implement and providing more flexibility for management. A lot of constraints are also seen by farmers regarding result-oriented measures. Advice, support, or training is strongly needed for implementation at a wider scale. Abstract: Throughout the last decades, both reactive and proactive incentive policies have been developed to support farmers implementing environmental and biodiversity friendly management practices. More recently, however, result-oriented agri-environment measures have also been designed, where farmers are remunerated based on the achievement of certain results (e.g. a specific number of plant species on grasslands) and not solely on the implementation of defined management practices. We analysed this specifically in the context of mountainous farming in different Alpine countries. We carried out 79 interviews with farmers in different case study regions in Germany, France, Austria, Italy, and Switzerland. They included also details regarding farmland and biodiversity management, as well as the farmers' perceptions of and involvement in result-oriented measures. Lastly, we asked farmers to suggest new future measures. Many of the farmers interviewed already engaged in agri-environment measures contracts, with a subset using result-oriented contracts. Farmer motivations to become involved with contracts included economic benefits and environmental preservation. Despite perceived constraints in the implementation of result-oriented measures, many farmers would prefer this approach, as it is seen as easier to implement and provides more flexibility to adapt its use to the specific conditions of their farm. In relation to biodiversity management, while many farmers would favour different types of grassland management measures to improve diversity of wild plants and animals (domesticated breeds and wild animals) on the farm, they experienced difficulty in articulating own suggestions for result-oriented measures. Our study shows that the result-oriented approach is an attractive option for many farmers, but a strong need for advice, support, or training would be necessary to implement such measures at a wider scale.